ANALISIS PENGARUH GAYA KEPEMIMPINAN MANAJER KEBUN TERHADAP SEMANGAT KERJA KARYAWAN DI PT. NIAGAMAS GEMILANG - Ari Hastini; Fadli Mulyadi; Rusmini (JURNAL AGRIMENT, 2019)
Along with the rapid progress on industrial sector also the expansion of oil palm plantation area, thus it will require a lot of human resource. In order to move and influence the employee, they need a leader to reach company’s goals. Purposes of this research are to identify the leadership style and work enthusiasm also to analyse the influence of estate Manager’s leadership style toward employees’ work enthusiasm in PT. Niagamas Gemilang. The method that used in this research is multiregression analysis with SPSS 22.0 and questioner. Respondent is divided in three classes which are all Field Assistant, all Foreman and 15% of Permanent Daily Employees in one Estate. The result showed that the Manager tend to apply task oriented leadership style. Furthermore, there was a significant influence from task oriented and employee oriented leadership style towards employee’s work enthusiasm both simultaneously and partially towards Field Asistant’s work enthusiasm. Meanwhile for Foreman and Permanent Daily Employee, there was no significant influence of the Manager’s leadership style on their work enthusiasm.This was caused by the form of organization structure, the direct supervisor of Foremans and Employees are not the Manager, therefore it would make sense if the leadership style that applied by the Manager has more and even greater influence toward Field Assistant whose direct supervisor is the Manager.